Sequence polymorphism of mitochondrial dna hvs-11 region of chinese population of peninsular Malaysia - Mutalib, Asrul Fahmi Abdul (Universiti Sains Malaysia, 2008)
The mitochondrial DNA hypervariable segment II (HVS-Iij sequence variations from various populations are less published compared to hypervariable segment I (HVS-1). The primary objective of this study is to determine the HVS-II sequence polymorphisms of the Chinese population and then use the data acquired to classify the mtDNA haplogroup. The study was carried out by using 3 7 samples from Chinese population of Peninsular Malaysia. The HVS•II of the mtDNA control region was amplified and sequenced. Polymorphisms were reported by aligning each sequence to the Cambridge Reference Sequence (CRS). A total of 57 polymorphisms were detected, which encompass 27 transitions and 20 transversion. By using the HVS•II sequence data, 22 samples were classified into superhaplogroup M (M7b 1, M8a, G2a, DSa, D4 and C) and 3 samples were classified into superhaplogroup N (R9a and N9a). The unclassified samples need further analysis for their classification.